Assessment of students’ knowledge about environmental health in College of Health and Medical Technology: A Cross-Sectional study - hussein, Sulaf; hasoon, Suhair (Iraqi National Journal of Nursing Specialties, 2013)
Objective: the aim of this study is to determine the level of students’ knowledge about the environmental health. Methodology: The cross-sectional study was conducted at the College of Health and Medical Technology in Baghdad city during the period from 1st march till 1st of July 2012. Data was collected by self-recording of a previously designed questionnaire to obtain socio-demographic information such as (age, gender, department, year of grade). Results: The highest rate of students were in the 2nd year followed by the 3rd year, highest rate of students had low level of knowledge followed by intermediate level of knowledge, while lowest rate of students on had high level of knowledge .Females had higher level of knowledge compared to males who had intermediate Level of knowledge; Students of pathological analysis department had high level of knowledge among other students, followed by students of anesthesia department. The lowest rate was among department the physiotherapy. A significant association between that low level of knowledge was among 1st (57.7%) and 2nd (50.7%) year students mainly , while high level of knowledge was mainly among 4th year (9.8%), and the intermediate level of knowledge was among 3rd year students in a rate of (53.3%) and 4th year in a rate of 50%. Recommendations: Include all the department of the college in environment health lectures as the issue is important for all student and not only the community health students.